2022
DOI: 10.1021/acsnano.2c00802
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Dichalcogenide Dimer Nanoantennas for Tailored Light–Matter Interactions

Abstract: Transition metal dichalcogenides have emerged as promising materials for nanophotonic resonators because of their large refractive index, low absorption within a large portion of the visible spectrum, and compatibility with a wide range of substrates. Herein, we use these properties to fabricate WS 2 double-pillar nanoantennas in a variety of geometries enabled by the anisotropy in the crystal structure. Using dark-field spectroscopy, we reveal multiple Mie resonances, to which we couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…This interest has grown even more after publication of several nanopatterning methods of TMDs and studies of optical phenomena in resulting TMD nanostructures. 14,15 Recent observations include high-index Mie resonances and anapole states in WS 2 nanodisks, 14 optical anisotropy in TMD slabs 7,9 and nanocones, 16 self-hybridization in TMD slabs 17,18 and nanotubes, 19 optical modes in lattices of TMD nanostructures, 20 improved second-harmonic generation in WS 2 and MoS 2 nanodisks, 21,22 high-index metamaterials, 23 nanoholes down to ∼20 nm, 24 dimer nanoantennas, 25 and TMD metamaterials with atomically sharp edges. 26 Theoretical predictions of large values of dielectric functions of TMDs and related vdW materials include density functional theory (DFT) studies, which confirm exceptionally high values and the anisotropic nature of permittivity tensors in these materials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interest has grown even more after publication of several nanopatterning methods of TMDs and studies of optical phenomena in resulting TMD nanostructures. 14,15 Recent observations include high-index Mie resonances and anapole states in WS 2 nanodisks, 14 optical anisotropy in TMD slabs 7,9 and nanocones, 16 self-hybridization in TMD slabs 17,18 and nanotubes, 19 optical modes in lattices of TMD nanostructures, 20 improved second-harmonic generation in WS 2 and MoS 2 nanodisks, 21,22 high-index metamaterials, 23 nanoholes down to ∼20 nm, 24 dimer nanoantennas, 25 and TMD metamaterials with atomically sharp edges. 26 Theoretical predictions of large values of dielectric functions of TMDs and related vdW materials include density functional theory (DFT) studies, which confirm exceptionally high values and the anisotropic nature of permittivity tensors in these materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These observations have led to a recently renewed interest in TMD optics and nanophotonics. This interest has grown even more after publication of several nanopatterning methods of TMDs and studies of optical phenomena in resulting TMD nanostructures. , Recent observations include high-index Mie resonances and anapole states in WS 2 nanodisks, optical anisotropy in TMD slabs , and nanocones, self-hybridization in TMD slabs , and nanotubes, optical modes in lattices of TMD nanostructures, improved second-harmonic generation in WS 2 and MoS 2 nanodisks, , high-index metamaterials, nanoholes down to ∼20 nm, dimer nanoantennas, and TMD metamaterials with atomically sharp edges …”
Section: Introductionmentioning
confidence: 99%
“…12,33 It inspired researchers to shift their attention to their bulk counterparts 34 since they preserve the advantages of monolayers, namely, large optical constants, 6 an asymmetrical optical response, 23,35 and excitonic dielectric function, 36 thanks to weak vdW bonding between layers. As a result, layered materials have already demonstrated great results in subdiffractional guiding, 23,37 integrated circuits, 38 strong light-matter coupling, [39][40][41] resonance nonlinear processes, 28,42 polaritonic transport, 23,43 anisotropic metasurfaces, 31,44 and photothermal conversion, 45 especially, in the case of transition metal dichalcogenides (TMDCs). In addition, recent works 40,[45][46][47][48] establish the fabrication processes of TMDC nanostructures that are compatible with widespread complementary metal oxide technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic layered nature of TMD crystals further provides record high optical anisotropy, 165 with advantages for the development of photonic components and devices. Recent reports have demonstrated that single disks of TMD crystals (Figure 7h), owing to their large refractive index, exhibit optical Mie resonances and anapole states 166 and can be fabricated with atomic precision in dimer nanoantennas 167 and optical metasurfaces (Figure 7i,j). 168 The versatility in the fabrication of TMD structures for photonic applications enables the generation of exciton plasmon polaritons in hybrid metal-TMD photonic gratings 169 or unidirectional nonlinear emission in metasurfaces 170 made entirely from bulk TMD crystals.…”
Section: All-dielectric Metasurfaces Similar To Individual Nanostruct...mentioning
confidence: 99%